State–Media Consensus on Going to War? Australian Newspapers, Political Elites, and Fighting the Islamic State. (October 2019) - Mulherin, Peter E.; Isakhan, Benjamin
This article assesses the link between the state and the media in their coverage of foreign policy decisions. It holds up to empirical scrutiny the claim that genuine press criticism can only occur within the bounds of political-elite debate. Taking the Australian government's 2014 decision to fight the Islamic State as its case study, it explores areas of consensus and dissensus between political discourse and the media. Conducting a qualitative analysis of three media frames used by major newspapers, it tests the "indexing hypothesis" and concludes that some press coverage went beyond the parameters of political-elite debate. This finding of independent criticism has implications beyond the present case study, as it helps us better understand the role of the media in democracies—specifically, holding governments to account when sending their nations to war.